(untitled) (Journal of Economic Research & Business Administration, 2017)
The article analyzes the existing approaches to the definition of entrepreneurial activity, the main existing methods for assessing entrepreneurial activity, their features, identified the main elements and components of entrepreneurial activity, as well as the importance of assessing the indicator of entrepreneurial activity for the effective management of business structures. The result of the analysis was its own definition of entrepreneurial activity.